Functional electrical stimulation (FES) for children and young people with cerebral palsy. Issue 11 (November 2019) - Singleton, Christine; Jones, Helen; Maycock, Lizz
Abstract: Evidence for functional electrical stimulation (FES) as a treatment option in adult neurological conditions has grown over the last 25 years. Children and young people with neurological conditions can also benefit from FES treatments but there are gaps in clinical knowledge, awareness and evidence which need addressing. Some of the known benefits of FES include safe walking with facilitation and exercise of 'normal' movement, muscle strengthening, joint range and proprioceptive improvements as well as spasticity reduction. There are similarities but also differences and challenges in applying FES between the adult and paediatric age groups. It is important to recognize these differences together with the need to alter techniques in applying FES for children. Birmingham has the largest paediatric FES service in the UK and the aim of this article is to share our knowledge and experience in providing FES as a treatment option for children and young adults with cerebral palsy.